Dopamine neuron glutamate release sites in the forebrain revealed by proximity - Martin, Alyssa; Caldwell, Megan; McKee, Paul; Ryndych, Darya; Fonseca, Philip; Mitchell, Clare; Fiore, Elizabeth; Shteyman, Gary; Field, Bianca; Trifilieff, Pierre; Chuhma, Nao; Antonios, Imad; et al. (Dopamine Society, 2022)
Keywords: dept.csc; ⛔ No DOI found

Computer Systems: Digital Design, Fundamentals of Computer Architecture and Assembly Language - Elahi, Ata (Springer Nature Switzerland AG, 2022)
Keywords: Assembly languages (Electronic computers); Computer engineering; Computer architecture; dept.csc; faculty_collection

Application of Time Series Analysis Methods to Assess the impact of COVID-19 on Carbon Dioxide Emission Reduction in Connecticut - Kiernan, Katherine A.; Wu, Hao; Mugno, Ray; Pang, Yulei (2022 IEEE International Conference on Big Data (Big Data), 2022)
The primary goals of this study are to determine if the datasets of positive COVID-19 test cases and CO2 emissions from Connecticut over the span of March 24th, 2020-October 31, 2021 are in any ways correlated. With climate change a prominent issue facing the entire world today, it is important to explore methods of providing records of past patterns of greenhouse gas emissions in order to inform decision making that could reduce future ones. Autoregressive integrated moving average (ARIMA) modeling is also implemented in this paper to provide forecasting based on CO2 emissions in CT starting from 2019. The most significant results from this paper are as follows: the CO2 emission data of transportation sectors including ground transportation, domestics aviation, and international aviation and weekly COVID-19 positive test cases data has a strong relationship during the first 28 weeks of the pandemic with a correlation of -86.34%. The CO2 emissions experienced on average a -22.96% change of pre-pandemic vs during initial quarantine conditions and at most a - 44.48% change when comparing the pre-pandemic mean to the during initial quarantine minimum value. Lastly, the ARIMA model found to have the lowest Akaike information criterion (AIC) was ARIMA (4,0,4). In conclusion, in the event of a collective global pandemic and lockdown conditions, less traveling resulting in a correlated decrease of CO2 emissions. This means that perhaps concentrated efforts on reducing unnecessary travel could help mitigate the levels of carbon dioxide emissions as a more long-term solution to climate change opposed to the pandemic’s short-term example.
0 citations (Crossref) [2023-10-31]
Keywords: ARIMA; CO2 emission; COVID-19; Carbon dioxide; Change points detection; Climate change; Correlation coefficient; Decision making; Greenhouse effect; Pandemics; Time series analysis; dept.csc; dept.mat

Comparing Machine Learning Models for Intron Classification - Kohnert, C.; Yu, N.; Rosenberg, P.; Torgerson, M.; Sobky, A.E.; Elkharboutly, R.; Seesi, S.A. (2022)
This work explores using Probabilistic Context Free Grammars and Artificial Neural Networks as possible machine learning models for classifying introns into major and minor introns. It presents an intron classification framework that combines probabilistic context free grammars and support vector machines. It also assesses the computational prediction power of these two models in comparison to the Position Weight Matrices technique, which is currently the exclusively used model for intron classification. The comparison is done through experimental analysis, and it shows promising results for Probabilistic Context Free Grammars and Artificial Neural Networks. © 2022 IEEE.
0 citations (Crossref) [2023-10-31]
Keywords: Artificial Neural Network; Position Weight Matrices; Probabilistic Context Free Grammars; U12 introns; U2 introns; dept.csc; intron classification; major introns; minor introns

Bad dream frequency predicts mental health needs during the SARS-CoV-2 pandemic - Simmons, Claire; McKee, Paul; Antonios, Imad; Smith, Anna; Sinnott-Armstrong, Walter (Journal of Affective Disorders Reports, 2022)
0 citations (Crossref) [2023-10-31]
Keywords: dept.csc; peer-reviewed

On error reduction by the symmetric rejection method in multi-stage biometric verification systems - Hossain, M.S.; Chen, J.; Rahman, K. (Pattern Analysis and Applications, 2022)
A multi-stage biometric verification system serially activates its verifiers and improves performance-cost trade-off by allowing users to submit a subset of the available biometrics. In the heart of a verifier in multi-stage systems lies the concept of ‘reject option’ where a reject region is used to identify a bad quality test sample. If the match-score falls inside the reject region, no binary (genuine/impostor) decision is made in the current stage and the verifier in the next stage is activated. Recent studies have demonstrated a significant promise of the ‘symmetric rejection method’ in choosing a suitable reject region for multi-stage verification systems. In this paper, we delve into the symmetric rejection method to gain more insights into its error reduction capabilities. Specifically, we develop a theory which mathematically proves that the symmetric rejection method reduces the false accept rate and false reject rate. Then, we empirically validate our theory. Results show that the symmetric rejection method significantly reduces the error rates, both the false accept rate and false reject rate. © 2022, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.
0 citations (Crossref) [2023-10-31]
Keywords: Authentication; Biometrics; Multi-stage system; Serial fusion; Symmetric rejection method; dept.csc; peer-reviewed

Review of Application of Machine Learning as a Screening Tool for Diagnosis of Obstructive Sleep Apnea - Aiyer, Ishan; Shaik, Likhita; Sheta, Alaa; Surani, Salim (Medicina, 2022)
Obstructive sleep apnea syndrome (OSAS) is a pervasive disorder with an incidence estimated at 5–14 percent among adults aged 30–70 years. It carries significant morbidity and mortality risk from cardiovascular disease, including ischemic heart disease, atrial fibrillation, and cerebrovascular disease, and risks related to excessive daytime sleepiness. The gold standard for diagnosis of OSAS is the polysomnography (PSG) test which requires overnight evaluation in a sleep laboratory and expensive infrastructure, which renders it unsuitable for mass screening and diagnosis. Alternatives such as home sleep testing need patients to wear diagnostic instruments overnight, but accuracy continues to be suboptimal while access continues to be a barrier for many. Hence, there is a continued significant underdiagnosis and under-recognition of sleep apnea in the community, with at least one study suggesting that 80–90% of middle-aged adults with moderate to severe sleep apnea remain undiagnosed. Recently, we have seen a surge in applications of artificial intelligence and neural networks in healthcare diagnostics. Several studies have attempted to examine its application in the diagnosis of OSAS. Signals included in data analytics include Electrocardiogram (ECG), photo-pletysmography (PPG), peripheral oxygen saturation (SpO2), and audio signals. A different approach is to study the application of machine learning to use demographic and standard clinical variables and physical findings to try and synthesize predictive models with high accuracy in assisting in the triage of high-risk patients for sleep testing. The current paper will review this latter approach and identify knowledge gaps that may serve as potential avenues for future research.
4 citations (Crossref) [2023-10-31] Number: 11
Keywords: ML; artificial intelligence; dept.csc; peer-reviewed; screening; sleep apnea

College student Fear of Missing Out (FoMO) and maladaptive behavior: Traditional statistical modeling and predictive analysis using machine learning - McKee, Paul C.; Budnick, Christopher J.; Walters, Kenneth S.; Antonios, Imad (PLOS ONE, 2022)
This paper reports a two-part study examining the relationship between fear of missing out (FoMO) and maladaptive behaviors in college students. This project used a cross-sectional study to examine whether college student FoMO predicts maladaptive behaviors across a range of domains (e.g., alcohol and drug use, academic misconduct, illegal behavior). Participants (N = 472) completed hard copy questionnaire packets assessing trait FoMO levels and questions pertaining to unethical and illegal behavior while in college. Part 1 utilized traditional statistical analyses (i.e., hierarchical regression modeling) to identify any relationships between FoMO, demographic variables (socioeconomic status, living situation, and gender) and the behavioral outcomes of interest. Part 2 looked to quantify the predictive power of FoMO, and demographic variables used in Part 1 through the convergent approach of supervised machine learning. Results from Part 1 indicate that college student FoMO is indeed related to many diverse maladaptive behaviors spanning the legal and illegal spectrum. Part 2, using various techniques such as recursive feature elimination (RFE) and principal component analysis (PCA) and models such as logistic regression, random forest, and Support Vector Machine (SVM), showcased the predictive power of implementing machine learning. Class membership for these behaviors (offender vs. non-offender) was predicted at rates well above baseline (e.g., 50% at baseline vs 87% accuracy for academic misconduct with just three input variables). This study demonstrated FoMO’s relationships with these behaviors as well as how machine learning can provide additional predictive insights that would not be possible through inferential statistical modeling approaches typically employed in psychology, and more broadly, the social sciences. Research in the social sciences stands to gain from regularly utilizing the more traditional statistical approaches in tandem with machine learning.
4 citations (Crossref) [2023-10-31]
Keywords: Alcohol consumption; Behavior; Cannabis; Drug interactions; Forecasting; Machine learning; Machine learning algorithms; Principal component analysis; dept.csc; dept.psy; peer-reviewed

Do Online Firms Individualize Search Results? An Empirical Analysis of Individualization on Amazon - Ahmed, Rasha; Al Seesi, Sahar; Ruiz Sánchez, Gerardo (Journal of Theoretical and Applied Electronic Commerce Research, 2022)
Online markets offer sellers access to buyers’ information and, thus, the potential to alter prices and products accordingly. In light of this, we undertook an empirical analysis to test for individualization on Amazon.com. We collect data from individuals recruited to shop for household items. Our results indicate evidence of individualization of search results and net prices (via coupons). We found, contrary to what was expected, that demographic, geolocation, and account information play an insignificant role in individualization of search results. Thus, we conclude that individualization is based on more dynamic information, e.g., online browsing behavior. This highlights the fact that sellers’ need for (and use of) buyer information goes beyond the simple information accessible from the buyers’ accounts to a more rigorous monitoring of buyers’ online behavior.
1 citations (Crossref) [2023-10-31] Number: 3
Keywords: Amazon; dept.csc; individualization; peer-reviewed; price discrimination

A machine learning based study to assess bone health in a diabetic cohort - Musleh, Saleh; Nazeemudeen, Anjanarani; Islam, Mohammad Tariqul; El Hajj, Nady; Alam, Tanvir (Informatics in Medicine Unlocked, 2022)
Diabetes mellitus (DM) and osteoporosis/osteopenia affect millions of people globally and are major health conditions in several countries including Qatar. Bone mineral density (BMD) is a widely accepted indicator for diagnosing osteoporosis (OP) and osteopenia (OPN). The best method for determining bone mineral density and OP/OPN risk is via dual energy X-ray absorptiometry (DXA) technology. The risk of osteoporosis-related fracture may increase for people with diabetes. Therefore, it is necessary to develop a system that can support the early detection of OP/OPN in diabetic patients. In this study, we analyzed Qatar diabetic cohorts including 500 subjects, among which 68 were OP/OPN (target) subjects and 432 were without osteoporosis/osteopenia (control) subjects. The objective of this study is to develop an ML model to distinguish diabetic OP/OPN patients from diabetic non-OP/non-OPN subjects based on their bone health indicators from full body DXA scan measurements. Based on our experiments, AdaBoost model performed the best for classifying the target group from the control group. 10-fold cross validation-based results indicate that the proposed ML model was able to distinguish the target group from the control group at 80% sensitivity, 96% specificity. To the best of our knowledge, our study is the first ML-based approach to detect the early onset of OP/OPN in diabetic cohort from Qatar. Our analyses revealed the higher level of lean mass, fat mass and bone mass for the control group compared to the target group. Higher levels of BMC, BMD from different body parts in the control group compared to the osteoporosis/osteopenia group indicate the protective effects of obesity on bone health in the Qatari diabetic cohort. Moreover, higher value of anthropometric measurements in troch, lumbar spine (L1, L2, L3, L4), pelvis and other body parts in the control group indicates that the WHO guideline can be applied to the Qatari diabetic cohort for the early detection of OP/OPN based on the proposed ML model. Further research on OP/OPN in diabetic patients is warranted in future to confirm the role of DM on bone health.
1 citations (Crossref) [2023-10-31]
Keywords: Bone mineral density; DXA; Diabetes; Dual energy X-ray absorptiometry; Machine learning; Osteopenia; Osteoporosis; Qatar Biobank (QBB); dept.csc; peer-reviewed

Barriers and facilitators to exclusive breastfeeding among Black mothers: A qualitative study utilizing a modified Barrier Analysis approach - Tran, Victoria; Reese Masterson, Amelia; Frieson, Tomeka; Douglass, Frankie; Pérez-Escamilla, Rafael; O'Connor Duffany, Kathleen (Maternal & Child Nutrition, 2022)
Breastfeeding has health benefits for both infants and mothers, yet Black mothers and infants are less likely to receive these benefits. Despite research showing no difference in breastfeeding intentions by race or ethnicity, inequities in breastfeeding rates persist, suggesting that Black mothers face unique barriers to meeting their breastfeeding intentions. The aim of this study is to identify barriers and facilitators that Black women perceive as important determinants of exclusively breastfeeding their children for at least 3 months after birth. Utilizing a Barrier Analysis approach, we conducted six focus group discussions, hearing from Black mothers who exclusively breastfed for 3 months and those who did not. Transcripts were coded starting with a priori parent codes based on theory-derived determinants mapped onto the Socioecological Model; themes were analysed for differences between groups. Facilitators found to be important specifically for women who exclusively breastfed for 3 months include self-efficacy, lactation support, appropriate lactation supplies, support of mothers and partners, prior knowledge of breastfeeding, strong intention before birth and perceptions of breastfeeding as money-saving. Barriers that arose more often among those who did not exclusively breastfeed for 3 months include inaccessible lactation support and supplies, difficulties with pumping, latching issues and perceptions of breastfeeding as time-consuming. Lack of access to and knowledge of breastfeeding laws and policies, as well as negative cultural norms or stigma, were important barriers across groups. This study supports the use of the Socioecological Model to design multicomponent interventions to increase exclusive breastfeeding outcomes for Black women.
3 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/mcn.13428
Keywords: barrier analysis; breastfeeding; dept.csc; dept.pch; focus group; peer-reviewed; public health; qualitative methods; social factors; sociocultural analyses

Autonomous Robot System for Pavement Crack Inspection Based Cnn Model - Sheta, A.; Mokhtar, S.A. (Journal of Theoretical and Applied Information Technology, 2022)
Maintaining the excellent state of the road is critical to secure driving and is an obligation of both transportation and regulatory maintenance authorities. For a safe driving environment, it is essential to inspect road surfaces for defects or degradation frequently. This process is found to be labor-intensive and necessitates primary expertise. Therefore, it is challenging to examine road cracks visually; thus, we must effectively employ computer visualization and robotics tools to support this mission. This research provides our initial idea of simulating an Autonomous Robot System (ARS) to perform pavement assessments. The ARS for crack inspection is a camera-equipped mobile robot (i.e., an Android phone) to collect images on the road. The proposed system is simulated using an mBot robot armed with an Android phone that gathers video streams to be processed on a server that has a pre-training Convolutional Neural Networks (CNN) that can recognize crack existence. The proposed CNN model attained 99.0% accuracy in the training case and 97.5% in the testing case. The results of this research are suitable for application with a commercial mobile robot as an autonomous platform for pavement inspections. © 2022 Little Lion Scientific.
Keywords: Automatic Detection; Autonomous Robot System; Crack Detection; Deep Neural Network; Pavement Crack; Road Maintenance; dept.csc; peer-reviewed; ⛔ No DOI found

Meta-heuristic Search Algorithms for Solving the Economic Load Dispatch Problem - Sheta, Alaa; Ali, Alaa; Baareh, Abdelkarim; Aljahdali, Sultan (2022 3rd International Conference on Artificial Intelligence, Robotics and Control (AIRC), 2022)
Economic load dispatch (ELD) is a challenge optimization problem to minimize the total cost of the thermally generated power that satisfies a set of equality and inequality constraints. We need to maximize the power network load under several operational constraints to solve this problem. Meanwhile, we need to minimize the cost of power generation and minimize the loss in the network transmission. Traditional optimization methods were used to solve such problems as linear programming. Meta-heuristic search algorithms have shown encouraging performance in solving various real-life engineering problems. This paper attempts to provide a comprehensive comparison between nine meta-heuristic search algorithms, including Genetic Algorithms (GAs), Particle Swarm Optimization (PSO), Crow Search Algorithm (CSA), Differential Evolution (DE), Salp Swarm Algorithm (SSA), Harmony Search (HS), Sine Cosine Algorithm (SCA), Multi-Verse Optimizer (MVO), and Moth-Flame Optimization Algorithm (MFO) for solving the economic load dispatch problem. Our developed results demonstrated that meta-heuristics search algorithms (i.e., CSA and DE) offer the optimal power set for each power station. These computed power fulfill the supply needs and maintain both minimum power costs and power losses in power transmission.
1 citations (Crossref) [2023-10-31]
Keywords: Costs; Economic Load Dispatch; Meta-heursitics Search algorithms; Optimization; Particle swarm optimization; Power distribution; Power transmission; Propagation losses; Search problems; Thermal loading; dept.csc

Incorporating deep learning into capacitive images for smartphone user authentication - Hossain, Md Shafaeat; Islam, Mohammad T.; Akhtar, Zahid (Journal of Information Security and Applications, 2022)
We incorporate deep learning techniques into capacitive images of body parts (ear, four fingers, and thumb) to improve the performance of user authentication in smartphones. Use of a capacitive touchscreen as an image sensor has several advantages, such as it is less sensitive to poor illumination conditions, occlusions, and pose variations. Also, it does not need an additional hardware like iris or fingerprint scanner. Use of capacitive images for user authentication is not new. However, the performance, specially, false reject rates (FRRs) of the state-of-the-art capacitive image-based systems are poor. In this paper, we focus on improving the performance and leverage deep learning. Deep learning techniques demonstrated spectacular performance in previous physical biometrics-based research. However, to our knowledge, effectiveness of deep learning is still unexplored in capacitive touchscreen-based user authentication. In order to bridge this research gap, we devise a multi-modal deep learning model, namely UASNet, and compare its performance with a large set of uni- and multi-modal baselines. Using the UASNet, we achieve an accuracy of 99.77%, an EER of 0.48%, and an FRR of 1.19% at FAR of 0.06%.
0 citations (Crossref) [2023-10-31]
Keywords: Biometrics; CNN; Capacitive images; Deep learning; Fusion; Smartphone; Touchscreen; User authentication; dept.csc; peer-reviewed

Cardiovascular Disease Diagnosis from DXA Scan and Retinal Images Using Deep Learning - Al-Absi, Hamada R. H.; Islam, Mohammad Tariqul; Refaee, Mahmoud Ahmed; Chowdhury, Muhammad E. H.; Alam, Tanvir (Sensors, 2022)
Cardiovascular diseases (CVD) are the leading cause of death worldwide. People affected by CVDs may go undiagnosed until the occurrence of a serious heart failure event such as stroke, heart attack, and myocardial infraction. In Qatar, there is a lack of studies focusing on CVD diagnosis based on non-invasive methods such as retinal image or dual-energy X-ray absorptiometry (DXA). In this study, we aimed at diagnosing CVD using a novel approach integrating information from retinal images and DXA data. We considered an adult Qatari cohort of 500 participants from Qatar Biobank (QBB) with an equal number of participants from the CVD and the control groups. We designed a case-control study with a novel multi-modal (combining data from multiple modalities—DXA and retinal images)—to propose a deep learning (DL)-based technique to distinguish the CVD group from the control group. Uni-modal models based on retinal images and DXA data achieved 75.6% and 77.4% accuracy, respectively. The multi-modal model showed an improved accuracy of 78.3% in classifying CVD group and the control group. We used gradient class activation map (GradCAM) to highlight the areas of interest in the retinal images that influenced the decisions of the proposed DL model most. It was observed that the model focused mostly on the centre of the retinal images where signs of CVD such as hemorrhages were present. This indicates that our model can identify and make use of certain prognosis markers for hypertension and ischemic heart disease. From DXA data, we found higher values for bone mineral density, fat content, muscle mass and bone area across majority of the body parts in CVD group compared to the control group indicating better bone health in the Qatari CVD cohort. This seminal method based on DXA scans and retinal images demonstrate major potentials for the early detection of CVD in a fast and relatively non-invasive manner.
17 citations (Crossref) [2023-10-31] Number: 12
Keywords: DXA; Qatar Biobank (QBB); cardiovascular diseases; deep learning; dept.csc; machine learning; peer-reviewed; retina

Zoom gesture analysis for age-inappropriate internet content filtering - Pulfrey, J.; Hossain, M.S. (Expert Systems with Applications, 2022)
The Internet contains large amounts of adult content. With only a few taps, or mis-taps, an under-aged user can be exposed to age-inappropriate content. Currently, this can be avoided by creating age-restricted profiles or restricting users to child-friendly applications (apps). However, these existing measures are time-consuming, laborious, and require a higher level of technical literacy than many parents can afford. We believe a better solution is to use a browser or an app that automatically detects the user's age then applies any appropriate content filters. For such a browser/app to be developed, we must learn that age estimation can indeed be performed with an acceptable rate of error. To that end, we created an Android app that collects biometric touchscreen data from elementary school, middle school, high school, and university students. Touch samples were collected from participants aged 5 to 61 on both smartphones and tablets. We focused exclusively on zoom-in and zoom-out touchscreen data samples. We made this decision because we found the zoom gesture to be rich with data and highly used among the most popular applications. Furthermore, we identify a niche within the current research landscape: no other machine learning experiments have leveraged the benefits of the zoom gesture for age estimation. We collected a total of 41,911 zoom data samples. From each zoom sample, 90 features were extracted. Those features were then used to train and test on six regressors and six classifiers to build a method that can accurately estimate the user's age from their touchscreen behavior. The regressors performed with the best mean absolute errors (MAEs) of 2.27 and 2.54 years for smartphones and tablets, respectively. The classifiers performed with the best accuracies of 90% and 91% for smartphones and tablets, respectively. Given these results, it is our belief that not only is touch-based age estimation viable, but developing a child-safe browser or a parental control app with this underlying technology is a worthwhile endeavor. © 2022 Elsevier Ltd
5 citations (Crossref) [2023-10-31]
Keywords: Age estimation; Child safety; Smartphone; Touch gesture; Zoom gesture; dept.csc; peer-reviewed

Memory based hybrid crow search algorithm for solving numerical and constrained global optimization problems - Braik, M.; Al-Zoubi, H.; Ryalat, M.; Sheta, A.; Alzubi, O. (Artificial Intelligence Review, 2022)
Crow Search Algorithm (CSA) is a promising meta-heuristic method developed based on the intelligent conduct of crows in nature. This algorithm lacks a good representation of its individuals’ memory, and as with many other meta-heuristics it faces a problem in efficiently balancing exploration and exploitation. These defects may lead to early convergence to local optima. To cope with such issues, we proposed a Memory based Hybrid CSA (MHCSA) with the use of Particle Swarm Optimization (PSO) algorithm. This hybridization approach was proposed to reinforce the diversity ability of CSA and balance its search abilities for promising solutions to achieve robust search performance. The memory element of MHCSA was initialized with the best solution (pbest) of PSO to exploit the most promising search areas. The best positions of the CSA’s individuals are improved using the best solution found so far (gbest) and (pbest) of PSO. Another flaw of CSA is the use of fixed flight length and awareness probability for crows to control exploration and exploitation features, respectively. This issue was circumvented here by replacing these constants with adaptive functions in order to provide a better balance between exploration and exploitation over the course of iterations. The competence of MHCSA was revealed by testing it on seventy-three standard and computationally complex benchmark functions. Its applicability was substantiated by solving seven engineering design problems. The results showed that the problem of early convergence was eliminated by MHCSA and that the balance of exploration and exploitation was further improved. Further, MHCSA ranked first among CSA, PSO, robust variants of CSA and other strong competing methods in terms of accuracy and stability. © 2022, The Author(s), under exclusive licence to Springer Nature B.V.
14 citations (Crossref) [2023-10-31] tex.author_keywords: Crow search algorithm; Meta-heuristics; Optimization techniques; Particle swarm optimization tex.coden: AIRVE tex.document_type: Article tex.source: Scopus
Keywords: Algorithm for solving; Balancing; Constrained global optimization; Constrained optimization; Crow search algorithm; Early convergence; Exploration and exploitation; Global optimization; Global optimization problems; Heuristic methods; Learning algorithms; Meta-heuristic methods; Metaheuristic; Optimization techniques; Particle swarm optimization (PSO); Search Algorithms; dept.csc; peer-reviewed

Enhanced cuckoo search algorithm for industrial winding process modeling - Braik, M.; Sheta, A.; Al-Hiary, H.; Aljahdali, S. (Journal of Intelligent Manufacturing, 2022)
Modeling of nonlinear industrial systems embraces two key stages: selection of a model structure with a compact parameter list, and selection of an algorithm to estimate the parameter list values. Thus, there is a need to develop a sufficiently adequate model to characterize the behavior of industrial systems to represent experimental data sets. The data collected for many industrial systems may be subject to the existence of high non-linearity and multiple constraints. Meanwhile, creating a thoroughgoing model for an industrial process is essential for model-based control systems. In this work, we explore the use of a proposed Enhanced version of the Cuckoo Search (ECS) algorithm to address a parameter estimation problem for both linear and nonlinear model structures of a real winding process. The performance of the developed models was compared with other mainstream meta-heuristics when they were targeted to model the same process. Moreover, these models were compared with other models developed based on some conventional modeling methods. Several evaluation tests were performed to judge the efficiency of the developed models based on ECS, which showed superior performance in both training and testing cases over that achieved by other modeling methods. © 2022, This is a U.S. government work and not under copyright protection in the U.S.; foreign copyright protection may apply.
4 citations (Crossref) [2023-10-31] tex.author_keywords: Cuckoo search algorithm; Industrial winding process; Linear model; Nonlinear model tex.coden: JIMNE tex.document_type: Article tex.source: Scopus
Keywords: Cuckoo search algorithms; Developed model; Industrial systems; Industrial winding process; Learning algorithms; Linear modeling; Model method; Model structures; Non-linear modelling; Nonlinear systems; Optimization; Parameter estimation; Performance; Process-models; Winding; Winding process; dept.csc; peer-reviewed

ALLD: Acute lymphoblastic leukemia detector - Musleh, S.; Islam, M.T.; Alam, M.T.; Househ, M.; Shah, Z.; Alam, T. (Studies in Health Technology and Informatics, 2022)
Acute Lymphoblastic Leukemia (ALL) is a life-threatening type of cancer wherein mortality rate is unquestionably high. Early detection of ALL can reduce both the rate of fatality as well as improve the diagnosis plan for patients. In this study, we developed the ALL Detector (ALLD), which is a deep learning-based network to distinguish ALL patients from healthy individuals based on blast cell microscopic images. We evaluated multiple DL-based models and the ResNet-based model performed the best with 98% accuracy in the classification task. We also compared the performance of ALLD against state-of-the-art tools utilized for the same purpose, and ALLD outperformed them all. We believe that ALLD will support pathologists to explicitly diagnose ALL in the early stages and reduce the burden on clinical practice overall. © 2022 The authors and IOS Press.
0 citations (Crossref) [2023-10-31] ISBN: 9781643682501 tex.author_keywords: Acute lymphoblastic leukemia; Computer aided diagnosis (CAD); Deep learning; Leukemia tex.document_type: Conference Paper tex.pubmed_id: 35062096 tex.source: Scopus
Keywords: Acute lymphoblastic leukaemias; Classification tasks; Computer; Computer aided diagnose; Computer aided diagnosis; Computer aided instruction; Deep Learning; Deep learning; Diseases; Healthy individuals; Humans; Individual-based; Medical informatics; Microscopic image; Mortality rate; Neural Networks; Performance; Precursor Cell Lymphoblastic Leukemia-Lymphoma; State of the art; acute lymphoblastic leukemia; dept.csc; human; peer-reviewed

Summarizing consumer reviews - Peal, M.; Hossain, M.S.; Chen, J. (Journal of Intelligent Information Systems, 2022)
E-commerce giants like Amazon rely on consumer reviews to allow buyers to inform other potential buyers about a product’s pros and cons. While these reviews can be useful, they are less so when the number of reviews is large; no consumer can be expected to read hundreds or thousands of reviews in order to gain better understanding about a product. In an effort to provide an aggregate representation of reviews, Amazon offers an average user rating represented by a 1- to 5-star score. This score only represents how reviewers feel about a product without providing insight into why they feel that way. In this work, we propose an AI technique that generates an easy-to-read, concise summary of a product based on its reviews. It provides an overview of the different aspects reviewers emphasize in their reviews and, crucially, how they feel about those aspects. Our methodology generates a list of the topics most-mentioned by reviewers, conveys reviewer sentiment for each topic and calculates an overall summary score that reflects reviewers’ overall sentiment about the product. These sentiment scores adapt the same 1- to 5-star scoring scale in order to remain familiar to Amazon users. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
1 citations (Crossref) [2023-10-31] tex.author_keywords: Affective computing; Amazon consumer reviews; Aspect-based sentiment analysis; Language summarization; Topic extraction tex.coden: JIISE tex.document_type: Article tex.source: Scopus
Keywords: AI techniques; Affective Computing; Amazon consumer review; Aspect-based sentiment analyse; Consumer reviews; Language summarization; Potential buyers; Sentiment analysis; Topic extraction; User rating; dept.csc; peer-reviewed

The linkage between bone densitometry and cardiovascular disease - Refaee, M.A.; Al-Absi, H.R.H.; Islam, M.T.; Househ, M.; Shah, Z.; Rahman, M.S.; Alam, T. (Studies in Health Technology and Informatics, 2022)
Dual-energy X-ray absorptiometry (DXA) has been traditionally used to assess body composition covering bone, fat and muscle content. Cardiovascular disease (CVD) has deleterious effects on bone health and fat composition. Therefore, early detection of bone health, fat and muscle composition would help to anticipate a proper diagnosis and treatment plan for CVD patients. In this study, we leveraged machine learning (ML)-based models to predict CVD using DXA, demonstrating that it can be considered an innovative approach for early detection of CVD. We leveraged state-of-the-art ML models to classify the CVD group from non-CVD group. The proposed logistic regression-based model achieved nearly 80% accuracy. Overall, the bone mineral density, fat content, muscle mass and bone surface area measurements were elevated in the CVD group compared to non-CVD group. Ablation study revealed a more successful discriminatory power of fat content and bone mineral density than muscle mass and bone areas. To the best of our knowledge, this work is the first ML model to reveal the association between DXA measurements and CVD in the Qatari population. We believe this study will open new avenues of introducing DXA in creating the diagnosis and treatment plan of cardiovascular diseases. © 2022 The authors and IOS Press.
0 citations (Crossref) [2023-10-31] ISBN: 9781643682501 tex.author_keywords: Bone densitometry; Cardiovascular disease; Dual-energy X-ray absorptiometry (DXA); Qatar Biobank (QBB) tex.document_type: Conference Paper tex.pubmed_id: 35062138 tex.source: Scopus
Keywords: Absorptiometry; Adipose Tissue; Biobanks; Biochemistry; Body Composition; Bone Density; Bone densitometry; Bone mineral density; Cardiology; Cardiovascular Diseases; Cardiovascular disease; Diagnosis; Diseases; Dual-energy X-ray; Dual-energy X-ray absorptiometry; Humans; Light absorption; Machine learning models; Muscle; Patient treatment; Photon; Qatar biobank; Treatment plans; X-ray absorptiometry; adipose tissue; body composition; bone density; cardiovascular disease; dept.csc; diagnostic imaging; human; peer-reviewed; photon absorptiometry